Dynamics of cochlear synaptopathy after acoustic overexposure - Liberman, Leslie D. (J Assoc Res Otolaryngol, 2015)
Recent work shows that acoustic overexposures causing only transient threshold elevation, and no hair cell loss, nevertheless can cause irreversible loss of the synapses between inner hair cells and cochlear nerve fibers (Kujawa and Liberman 2009). This cochlear synaptopathy, which is selective for the subset of sensory fibers with high thresholds and low spontaneous rates (Furman et al. 2013), appeared fully developed at 24-h post-exposure and showed no recovery by 8 weeks. However, prior studies of this synaptopathy counted only pre-synaptic ribbons, did not examine post-exposure times less than 24 h, and did not analyze the spatial patterns of degeneration around the hair cell circumference. Here, we immunostained for pre-synaptic ribbons, post-synaptic terminals and glutamate receptor patches, as well as the hair cell cytoplasm in noise-exposed and control mice to address the dynamics and spatial organization of the synaptopathic process as a function of post-exposure time from 0 h to 2 weeks. Our analysis showed that the loss of synaptic elements is nearly complete immediately after the 2-h exposure, that there is a reversible downregulation of gluR expression in the peripheral terminals which may be part of a protective mechanism, that there may be reversible reorganization of synaptic locations immediately after exposure, and that the spatial patterns are consistent with the idea that low-SR fibers are mainly found on the modiolar face of the hair cell and are the most vulnerable to noise-induced degeneration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10162-015-0510-3) contains supplementary material, which is available to authorized users.